858 questions

74.1k answers

47.5k users

Welcome to Get Answer from One Click, where you can ask questions and receive answers from other members of the community.
0 votes
(x-a)(x-b) is equal to x^2-xb-ax-ab= x^2 -x(b+a) –ab or = x^2 -b(x+a) –ax.

The x minus a and b takes the quadratic formula and includes steps that should govern with above formula by operating and come across in an identify of same sort.

This is binomial expansion of the form and each of these terms can be resultant value.
asked Jul 9, 2021 in Education by (520 points)

1 Answer

0 votes
<a href="">puma rbr cap</a> <a href="">ray ban light ray frames</a> <a href="">teddy bridgewater broncos t shirt</a> <a href="">shein botanical print dress</a> <a href="">grey crew neck jumper mens</a> <a href="">pandora black multi strand bracelet</a>
answered Jun 12, 2022 by vpoloni

Related questions

0 votes
0 answers
76 views asked Feb 2, 2021 in Education by manish
0 votes
0 answers